Stanisław Borowski jako badacz dziejów Wielkopolski - Topolski, Jerzy (Wydział Prawa i Administracji UAM, 1981)
Stanisław Borowski was a scientist, who combined integrally competences of economic historian, demographer and economist. Thanks to methodological and theoretical values He joined the group of best Polish historians and demographers. The Wielkopolska region, considered often with Pomerania and Silesia together, was a main subject and field of research for Professor Borowski, allowing to investigate and to verify regularities of socio-economic and demographic development. S. Borowski started His scientific output with an extensive study devoted to development of labour mechanization in Wielkopolska agriculture in the years 1823 - 1918. Further research aimed at exploration of social and economic action allowing to explain changes in agriculture and situation of peasants in Wielkopolska in the 19-th century. The first place was then occupied by research on influence of incorporating the country in the sphere of market. S. Borowski published two voluminous books on that subject. They significantly enriched our knowledge about the Wielkopolska's country and agriculture in the 19-th century. Simultaneously demographic structure of Wielkopolska in the course of ages was examined by S. Borowski. Demographic changes were always explained in the light of historic events and in the course of phenomena examination in their long-run development. The research pivot is showing and explaining processes of transition from traditional pre-industrial population development model to a modern model, and so analysis of demographic revolution. In that context S. Borowski examined among others factors that determined the process of dying out, questions of emigration from the Polish lands under German sector in the 19-th century and demographic development of Wielkopolska from the end of the 16-th to the 20-th century. A few studies were devoted to methodological considerations on statistical sources. They are original thoughts, still having their full inspirational value. Particularly, penetration in analysis of appraisal criterions of statistical sources should be underlined. S. Borowski was a modern scientist. He combined comprehensive empirical studies with theoretical and methodological thought in His research.
Stanisław Borowski as a Researcher of Wielkopolska History